A Review of Bioactive Compounds of Guava: Biosynthesis and Mechanism Against Multidrug-Resistant (MDR) Bacteria - Ilagan, Cedrick Piolo M; Austria, Alyssa Eunice S; Bunao, Kathleen Desiree S; Reyes, Ian Leoj L; Tumbale, Jan Alyssa P; Loyzaga, Andrea Mae M; Petalcorin, Kristina Maria R (Asian Journal of Biological and Life Sciences)
Aim/Background: Antimicrobial resistance remains to be a “silent” pandemic that immensely affects global populations and imminently challenges medical professionals on infection control and patient management. In combating such a global health crisis, overarching actions on antibiotic innovation potentially fill the gap against multidrug resistance. In that light, P sidium guajava Linnaeus, locally known as guava, is used in folk and traditional medicine for a variety of ailments. Focusing on antimicrobial activity, several guava-derived bioactive compounds (GBC) have provided guava with its antimicrobial properties against bacterial invasion. As such, the evaluation of guava’s antimicrobial activity against multidrug-resistant (MDR) bacteria interrelated with an understanding of the biosynthesis and mechanism of GBCs would be the highlight of this paper. Materials and Methods: While employing a systematic narrative approach, a total of 570 publications were gathered using Zotero from various library databases. Towards the conduct of the stratified screening, only 15 journals have satisfied the eligibility criteria. These publications expound on the biosynthesis and mechanisms of GBCs, and their activity against MDR bacteria. Results and Conclusion: Extensive analysis of collected literature has revealed that GBC production has been associated with the guava’s photosynthetic ability that passes through various pathways. Whereas, most GBCs specify an inhibition mechanism as the predominant antimicrobial action. As such, guava extracts, depending on the extraction solvent and guava part used, provide remarkable in vitro antimicrobial activity against MDR bacteria. With the emerging antimicrobial applications of guava, further studies shall be explored specifically on antibiotic innovation such as synergistic studies, in vivo studies, and clinical trials.
Keywords: Biosynthesis; Guava; Mechanism; Multidrug-Resistant Bacteria; Phytochemicalsm